Os princípios políticos do programa BH cidadania: o olhar de profissionais da Secretaria Municipal Adjunta de Esportes - Carolina Gontijo Lopes (2012)
Working with leisure policies in public spaces in Brazil is a possibility of intervention for professionals from the area of physical education. This reality requires from the professionals an understanding of the new forms of conducting social policy as an articulation of political principles. Therefore, I will treat this problem to ascertain the advances and limits in relation to the governmental management of public leisure policies. During the process of changes in the management of public policies the city administration of Belo Horizonte implements in 2002 the program BH Cidadania guided by the principles of intersectoriality, decentralization, popular participation and territoriality. The program uses these guidelines to treat social inclusion of families that reside in socially vulnerable territories by proposing to implement integrated unites of professional activity into the public sphere. In this context, I analyzed understanding of professionals who work for the Municipal Deputy Secretary of Sports (SMAES) in the referred program as technical analysts for these political principles. The qualitative investigation involved descriptive reports about the principles and narrations of the daily practices as they were told to them through the categories of organizational structures, operational culture, accessibility of services, professional autonomy, empowerment of subjects and territory. The adopted strategy consisted of bibliographic and field research. Bibliographical research sought books and journals that addressed social and leisure policies as well as their political principles. The field research included observations of the professionals‘ routine actions in their work spaces: internal meetings among sectors and with representatives of the population. 13 semi-structured interviews with all analysts were conducted, as well. The content analysis undertook a matching of empirical data with similarities and contrapositions found in reports addressed to those categories that seek to guide the discussion in the final report. In order to allow professionals to work with the complexity of these territories, organizational structures as proposed by the program should comprehend locally integrated actions: involving the different sectors of public service, of social institutions and community‘ representatives. To this end, this reconfiguration finds deadlocks resulting from the resistance of traditional sectoral forms of activities, reduced popular participation and from the professional hierarchy in social management, limiting technical acknowledgement of different areas. Nevertheless, in the tensions among technical interests, government and population the expansion of the program reverberates in the following ways: an increased accessibility to services by the attended, a broadening of staff and employment and in preoccupations with the actions‘ and professionals‘ qualification and the insertion of different dimensions of popular participation. However, each core of the program as it is shaped by characteristics of the territoriality shows specifications in the degree of principal adherence. Thus, the analysts‘‘ understanding of the principles permeated conforming to the ways that they were adhered, articulated and reproduced in the daily work experiences of BH Cidadania. In this way new possibilities are aggregated and the problems for professional intervention in leisure policies are identified